2018
DOI: 10.1097/nne.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Instructional Methods for Screening, Brief Intervention, and Referral to Treatment for Substance Use in Nursing Education

Abstract: Most nursing programs lack curriculum on substance use. This project evaluated 3 didactic instructional methods for teaching baccalaureate nursing students about screening, brief intervention, and referral to treatment for substance use. In-person, asynchronous narrated slides and interactive online instructional methods were all effective in developing students’ competency; however, active learning methods (in-person and interactive online course) were more effective in changing students’ attitudes about thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 23 publications
1
31
0
2
Order By: Relevance
“…Site coordinators' positive opinions of the SBIRT training were consistent with numerous published studies focused on nursing students as trainees (Mitchell et al, 2013;Gotham et al, 2015;Knopf-Amelung et al, 2018). The curricular aspects, described in Figure 1, appeared to match coordinators' expectations, and the order in which they were taught was perceived as logical.…”
Section: Discussionsupporting
confidence: 79%
“…Site coordinators' positive opinions of the SBIRT training were consistent with numerous published studies focused on nursing students as trainees (Mitchell et al, 2013;Gotham et al, 2015;Knopf-Amelung et al, 2018). The curricular aspects, described in Figure 1, appeared to match coordinators' expectations, and the order in which they were taught was perceived as logical.…”
Section: Discussionsupporting
confidence: 79%
“…Addiction curriculum is not standard across all NP and CNM school training or even in their core pregraduate training. A survey conducted of baccalaureate nursing programs across the Northeast reported an average of 1–5 hr of didactics about substance use disorder training and these results reflected no change from a similar survey conducted in the 1980s (Hoffman & Heinemann, 1987; Knopf‐Amelung et al., 2018; Murphy‐Parker, 2013). Similar concerns have been raised about medical school education, prompting the American College of Obstetricians and Gynecologists (ACOG) to recommend additional resident curriculum particularly related to opioid use disorder and opioid prescription.…”
Section: Discussionmentioning
confidence: 90%
“…To sustain SBIRT use in simulation and future practice, faculty sought ways to direct student learning, simplify content, and provide more active and engaged learning experiences. In a study that compared instructional methods for teaching SBIRT, researchers found that active learning methods (in‐person and interactive online activities) were more effective in changing students' attitudes and perceptions about their role in screening patients when compared to asynchronous narrated slides (Knopf‐Amelung et al, ). In this study, simplifying and highlighting difficult skills through active learning experiences helped to refine the delivery method and provided students with the ability to prioritize and focus on techniques to master prior to simulation day.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%